Integrating Critical Thinking Through Teachers’ Questioning Strategies in the Merdeka Curriculum for EFL Students of Islamic Senior High Schools - Shoolihah, Dwindah Mar'ah; Muniroh, Siti; Anugerahwati, Mirjam (JOLLT Journal of Languages and Language Teaching, 2026)
Critical thinking (CT) is determined as one of Indonesian senior high school’s graduate profiles in Merdeka Curriculum, and this policy suggests teachers to nurture students’ critical thinking, which focuses on students’ ability of analysing, evaluating and creating narrative and exposition texts. This qualitative study investigates on how the Pre-Service EFL Teachers’ (PSETs) inserted CT in their questioning strategies to teach narrative and exposition texts for the eleven graders of Islamic senior high school (Madrasah Aliyah) in Ponorogo. This qualitative case study captured PSETs’ questioning strategies implemented during their internship. Four PSETs were observed and interviewed to gather data about types of questioning strategies they implemented. The findings revealed that six types of questioning strategies have been implemented, namely structuring, directing, pitching, rhetorical, probing, and pausing. Then, the researchers identified six questioning strategy types and determined that four types of questioning strategies, such as directing, rhetorical, probing, and pausing effectively engaged students in higher-order cognitive processes aligned with critical thinking integration in learning activities such as, analyzing, evaluating, and creating narrative and exposition texts. In the process of creating narrative and exposition texts, the students hesitated to write their own and need scaffolding learning. The students always ensure their paragraph to PSETs. Hence, PSETs have to assist them optimally. In addition, the study also documents implementation challenges faced by pre-service teachers and proposes practical solutions.